2016
DOI: 10.1121/2.0000298
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the exposure of animals to acoustic disturbance: Towards an understanding of the population consequences of disturbance

Abstract: An essential component of risk assessment is identification whether individuals will be exposed to a risk. This requires information on the proportion of the population exposed, for how long, and during what activity (i.e., feeding, migrating, and breeding). Using satellite telemetry data for humpback and blue whales feeding and migratory regions in Antarctica, California, and Bering Sea, we modeled the potential exposure of individuals to an acoustic disturbance. Foraging and transit regions along the tracks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…The spatial and temporal overlap between the stressor and the focal animals determines the probability of exposure. This overlap is influenced by the patterns by which the stressor is produced at the source and propagates through the environment (Merchant, Faulkner, & Martinez, ) and the animals' residence time in the area where exposure may occur (Costa, Hückstädt, et al., ). Residence time is determined inter alia by the size of individual home ranges, the motivation underlying the use of the area of interest (e.g., whether the area contains foraging patches or is used solely for transit), and any migratory behavior.…”
Section: Estimating Levels Of Exposure In the Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial and temporal overlap between the stressor and the focal animals determines the probability of exposure. This overlap is influenced by the patterns by which the stressor is produced at the source and propagates through the environment (Merchant, Faulkner, & Martinez, ) and the animals' residence time in the area where exposure may occur (Costa, Hückstädt, et al., ). Residence time is determined inter alia by the size of individual home ranges, the motivation underlying the use of the area of interest (e.g., whether the area contains foraging patches or is used solely for transit), and any migratory behavior.…”
Section: Estimating Levels Of Exposure In the Populationmentioning
confidence: 99%
“…The spatial and temporal overlap between the stressor and the focal animals determines the probability of exposure. This overlap is influenced by the patterns by which the stressor is produced at the source and propagates through the environment (Merchant, Faulkner, & Martinez, 2018) and the animals' residence time in the area where exposure may occur (Costa, Hückstädt, et al, 2016).…”
Section: E S Timating Le Vel S Of E Xp Osure In the P Opul Ati Onmentioning
confidence: 99%
“…Similarly, the probability of exposure to disturbance within a given location appeared to matter more than the effect exposure had on feeding performance. Exposure rates to stressors have been shown to have a strong influence on the predicted effects of disturbance (Christiansen and Lusseau 2015, Costa et al 2016, Nabe-Nielsen et al 2018, Pirotta et al 2018a. Applications of our model to management requires information on the characteristics of the stressors and the associated dose-response curves (Harris et al 2018).…”
Section: Discussionmentioning
confidence: 97%
“…For example, Costa et al (2016) demonstrated that a small affected area and short activity period may result in many individuals being disturbed if the activity overlaps with a migration corridor and time period. This will be determined by a variety of factors that affect the distribution of individuals in space and time, including the size of a population's range, the size of individual home ranges, and individual movement patterns.…”
Section: Identifying a "Set Threshold" For Questionmentioning
confidence: 99%
“…This will be determined by a variety of factors that affect the distribution of individuals in space and time, including the size of a population's range, the size of individual home ranges, and individual movement patterns. For example, Costa et al (2016) demonstrated that a small affected area and short activity period may result in many individuals being disturbed if the activity overlaps with a migration corridor and time period. However, these individuals may only be briefly exposed to disturbance.…”
Section: Decision Framework Questionsmentioning
confidence: 99%